The amount and types of fatty acids acutely affect insulin, glycemic and gastrointestinal peptide responses but not satiety in metabolic syndrome subjects - Chang, Chee Yan; Kanthimathi, M.S.; Tan, Alexander Tong Boon; Nesaretnam, Kalanithi; Teng, Kim-Tiu (Springer, 2018)
Purpose: Limited clinical evidence is available on the effects of amount and types of dietary fats on postprandial insulinemic and gastrointestinal peptide responses in metabolic syndrome subjects. We hypothesized that meals enriched with designated: (1) amount of fats (50 vs 20 g), (2) fats with differing fatty acid composition (saturated, SFA; monounsaturated, MUFA or n-6 polyunsaturated fatty acids, PUFA) would affect insulinemic and gastrointestinal peptide releases in metabolic syndrome subjects. Methods: Using a randomized, crossover and double-blinded design, 15 men and 15 women with metabolic syndrome consumed high-fat meals enriched with SFA, MUFA or n-6 PUFA, or a low-fat/high-sucrose (SUCR) meal. C-peptide, insulin, glucose, gastrointestinal peptides and satiety were measured up to 6 h. Results: As expected, SUCR meal induced higher C-peptide (45 %), insulin (45 %) and glucose (49 %) responses compared with high-fat meals regardless of types of fatty acids (P < 0.001). Interestingly, incremental area under the curve (AUC0-120min) for glucagon-like peptide-1 was higher after SUCR meal compared with MUFA (27 %) and n-6 PUFA meals (23 %) (P = 0.01). AUC0-120min for glucose-dependent insulinotropic polypeptide was higher after SFA meal compared with MUFA (23 %) and n-6 PUFA meals (20 %) (P = 0.004). Significant meal x time interaction (P = 0.007) was observed for ghrelin, but not cholecystokinin and satiety. Conclusions: The amount of fat regardless of the types of fatty acids affects insulin and glycemic responses. Both the amount and types of fatty acids acutely affect the gastrointestinal peptide release in metabolic syndrome subjects, but not satiety.